2019
DOI: 10.3389/fmicb.2019.00901
|View full text |Cite|
|
Sign up to set email alerts
|

Surveillance and Genomics of Toxigenic Vibrio cholerae O1 From Fish, Phytoplankton and Water in Lake Victoria, Tanzania

Abstract: The occurrence of toxigenic Vibrio cholerae O1 during a non- outbreak period in Lake Victoria was studied and genetic characteristics for environmental persistence and relatedness to pandemic strains were assessed. We analyzed 360 samples of carps, phytoplankton and water collected in 2017 during dry and rainy seasons in the Tanzanian basin of Lake Victoria. Samples were tested using PCR ( omp W and ctx A) with DNA extracted from bacterial is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 77 publications
8
36
0
Order By: Relevance
“…In contrast to our study, the ESBLproducing bacteria reported in tilapia from the Mwanza region by Moremi et al (2016b) included a much more diverse population of bacterial species, a variety of ESBL genes, and no indication of a clonal relationship. The occurrence of genes encoding for resistance to metals such as copper, cobalt, zinc, cadmium, and mercury, and also genes encoding resistance to detergents is similar to previous findings in fish and aquatic environment of the Lake Victoria; the genes have been reported to play a role in environmental persistence support in bacterial survival (Moremi et al, 2016b;Hounmanou et al, 2019). Most of metal resistance genes were located on the chromosome, whereas ESBL genes were mostly located on the plasmids, except that all four ST636 isolates harbored a chromosomally located bla CTX−M−15 gene, and it is uncertain to what extent exposure to metals, for example, used as livestock feed additives and as pollutants in aquatic environments, may play a role as co-selectors of ESBL resistance.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to our study, the ESBLproducing bacteria reported in tilapia from the Mwanza region by Moremi et al (2016b) included a much more diverse population of bacterial species, a variety of ESBL genes, and no indication of a clonal relationship. The occurrence of genes encoding for resistance to metals such as copper, cobalt, zinc, cadmium, and mercury, and also genes encoding resistance to detergents is similar to previous findings in fish and aquatic environment of the Lake Victoria; the genes have been reported to play a role in environmental persistence support in bacterial survival (Moremi et al, 2016b;Hounmanou et al, 2019). Most of metal resistance genes were located on the chromosome, whereas ESBL genes were mostly located on the plasmids, except that all four ST636 isolates harbored a chromosomally located bla CTX−M−15 gene, and it is uncertain to what extent exposure to metals, for example, used as livestock feed additives and as pollutants in aquatic environments, may play a role as co-selectors of ESBL resistance.…”
Section: Discussionsupporting
confidence: 85%
“…al, 2018; also, the nding of this study in regards to most of the isolates except one belonging to the O1 serotype are consistent with other studies elsewhere, these studies attributed this to the presence of the rfbV-O1 gene in isolates classi ed as O1 (5). Unlike a similar study done in the East African region (5) in which MLST revealed that their isolates belonged to a single sequence type (ST), ST69, this study revealed that the isolates belonged to two STs namely ST69 and ST515. Strains of V. cholerae belonging to the ST515 have been reported elsewhere (9).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the World Health Organization (WHO) recommendations (https://www.who.int/topics/cholera/publications/WHO_CDD_SER_91_15/en/) in regards to the management of cholera with oral rehydration salts in addition to antibiotics namely streptomycin, aminoglycosides, trimethoprim, fosfomycin, uoroquinolones, sulphonamides, chloramphenicol/ orfenicol, and tetracyclines, this study reports genotypic resistance in the isolates to the same antibiotics. Similar resistance has been reported in similar studies done in the East African region and elsewhere (5,(15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations